Genomic profiling of multiple primary cancers including synchronous lung adenocarcinoma and bilateral malignant mesotheliomas: Identification of a novel BAP1 germline variant. Issue 10 (24th June 2020) - Shinozaki‐Ushiku, Aya; Kohsaka, Shinji; Kage, Hidenori; Oda, Katsutoshi; Miyagawa, Kiyoshi; Nakajima, Jun; Aburatani, Hiroyuki; Mano, Hiroyuki; Ushiku, Tetsuo
Abstract : We report a case with a rare combination of synchronous lung adenocarcinoma and bilateral malignant pleural mesotheliomas in a 70‐year‐old male without asbestos exposure. He metachronously developed peritoneal malignant mesothelioma, intrahepatic cholangiocarcinoma, urothelial carcinoma of the bladder and prostatic adenocarcinoma. Immunohistochemistry revealed complete loss of BAP1 expression in all seven lesions. Targeted next generation sequencing using Todai OncoPanel identified a novel germline variant (c.1565_1566del, p.P522Rfs*14) of BAP1 . Additionally, different nonsynonymous somatic mutations of BAP1 were identified in four lesions including lung adenocarcinoma, malignant pleural and peritoneal mesotheliomas, and bladder cancer. The remaining two lesions had different somatic mutations in genes other than BAP1 . Multiple BAP1‐deficient cancers that developed in a single patient suggest the newly identified germline variant of BAP1 gene to be pathogenic and this case expands the clinical spectrum of BAP1‐tumor predisposition syndrome. Screening for BAP1 status is highly recommended in cases with a similar combination of cancers.